2017
DOI: 10.2134/jeq2016.04.0125
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungal Association in Genetically Modified Drought‐Tolerant Corn

Abstract: The commercial use of genetically modified (GM) plants has significantly increased worldwide. The interactions between GM plants and arbuscular mycorrhizal (AM) fungi are of considerable importance given the agricultural and ecological role of AM and the lack of knowledge regarding potential effects of drought-tolerant GM corn ( L.) on AM fungal symbiosis. This work studied AM fungal colonization in five corn lines growing under two different irrigation regimes (30 and 100% of soil field capacity [SFC]). Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Among the fungi enriched in the Italian MM soil were Leotiomycetes and Glomeromycetes . Members of Leotiomycetes are known as maize endophytes ( Wang et al, 2006 ) and Glomeromycetes are well-known as arbuscular mycorrhizal symbionts of maize, including the enriched genus Entrophospora ( Na Bhadalung et al, 2005 ; Colombo et al, 2017 ). Actually, the genus Entrophospora was enriched in the MM bulk soil rather than in the rhizosphere (Supplementary Table 6B).…”
Section: Discussionmentioning
confidence: 99%
“…Among the fungi enriched in the Italian MM soil were Leotiomycetes and Glomeromycetes . Members of Leotiomycetes are known as maize endophytes ( Wang et al, 2006 ) and Glomeromycetes are well-known as arbuscular mycorrhizal symbionts of maize, including the enriched genus Entrophospora ( Na Bhadalung et al, 2005 ; Colombo et al, 2017 ). Actually, the genus Entrophospora was enriched in the MM bulk soil rather than in the rhizosphere (Supplementary Table 6B).…”
Section: Discussionmentioning
confidence: 99%
“…The sunflower (Helianthus annuus) Hah-4 gene was overexpressed in the maize plants to elucidate its role in mitigating the drought stress. The study revealed the crucial role of Hah-4 gene in increasing the resistance of maize plants against drought stress without hindering the agronomic traits and colonization of root Arbuscular mycorrhizal fungi activity [61]. The accumulation of ABA in the leaf is significant and plays a key role in maintaining normal plant growth under drought stress [62].…”
Section: Drought Stressmentioning
confidence: 98%
“…Hamonts et al (2018) demonstrated that sugarcaneassociated bacterial assemblage is primarily determined by plant compartment, followed by other factors such as the growing region and sugarcane variety. Indeed, plant genotype is responsible for some of the variations observed in root microbiomes, suggesting an active role of the host in the establishment of the communities (Colombo et al, 2017). Additionally, we also found a stronger correlation between the relative metrics of bacterial diversity and environmental factors in TG compared with those in WT, especially for the TC and TN contents ( Figures 1C,D, 2B), suggesting that the changes in the soil environment of the root microbiome influence the bacterial community diversity.…”
Section: Variation In Bacterial Community Diversity In Tg Sugarcanementioning
confidence: 99%